Factors affecting the adoption of organic agricultural standards among members of community enterprises in Roi Et Province, Thailand - Prawat, S.; Mankeb, P.; Chulilung, P.; Charoenkittayawut, S.; Khermkhun, J. (International Journal of Agricultural Technology, 2025)
The level of adoption of organic agricultural standards in crop production among members of community enterprises in Roi Et Province was assessed which based on the Certification Alliance Organic Standards. The findings revealed that four components including maintenance of organic management practices, pest and disease management, conversion to organic production, and enclosed cropping systems, were adopted at a very high level. The remaining components, including land and water management, contamination prevention, biodiversity, crop selection, and breeding, showed high levels of adoption. Split and parallel production received the lowest score but remained within the high adoption range. In addition, multiple regression analysis showed that experiences in organic farming, knowledge related to organic farming, and attitude towards organic farming positively and statistically influenced the level of adoption of organic agricultural standards among members of community enterprises in Roi Et Province.